PENGARUH BEBAN KERJA DAN KEPUASAN KERJA TERHADAP TURNOVER INTENTION KARYAWAN DI PT. FIF GROUP CABANG BATURAJA - Fiter Rio Perdinan; Dyah Ayu Putriani; Tati Herlina (Ekonomika, 2025)
This study aims to determine the effect of workload and job satisfaction on turnover intention among employees at PT FIF Group Baturaja Branch. Data collection was conducted through the distribution of questionnaires. The population consists of 40 employees at PT FIF Group Baturaja Branch. The data analysis technique used is Multiple Linear Regression using SPSS 21.The partial analysis results indicate that workload significantly affects turnover intention among employees, with a t-value (6.398) > t-table (2.026). The job satisfaction variable also significantly affects turnover intention, with a t-value (6.699) > t-table (2.026). Simultaneously, workload and job satisfaction significantly affect turnover intention, with an F-value (64.047) > F-table (3.25). The coefficient of determination (RÂ²) obtained is 0.776, indicating that 77.6% of the variation in turnover intention is influenced by workload and job satisfaction, while the remaining 22.4% is influenced by other factors such as motivation, work engagement, absenteeism, stress, and job performance (Afandi, 2021:77).